'Hanging out with mates': Friendship quality and its effect on academic endeavours and social behaviours. (August 2013) - Irwin, Michael
This article examines what it means to 'hang out with mates' and the effect that 'hanging out' has on boys' academic success and behaviours. The research was conducted in three geographic and socio-economic diverse secondary schools within New Zealand using 200 boys aged between 12 and 18 years both as participants and researchers. The research participants claimed that 'hanging out with mates' was a crucial activity during adolescence and an important reason for going to school. Adolescent boys who developed close male friendships perceived a variety of benefits that strengthened and protected them from the many social and academic pressures that arise during adolescence. 'Hanging out with mates' was perceived to have positive effects on school retention and achievement as boys moved into the upper levels of schooling. Boys claimed their mates acted as a buffer between peer group and academic stressors; as well as offering a secure environment from which to develop concepts of self.